Online compulsive buying behavior and its association with internet addiction, self-esteem, impulsiveness, and emotional distress among nursing students - Priyanshi Dixit; Uma Phalswal; Anjali Rathee; Yumnam Surbala Devi (Industrial Psychiatry Journal)
Background: Compulsive buying behavior [CBB] or pathological buying (PB) is a psychiatric disorder of growing recognition and many psychosocial factors have been proposed to predispose or precipitate this predicament. Aim: To find out the association of compulsive buying behavior, emotional distress, self-esteem, internet addiction, and impulsiveness among nursing students. Materials and Methods: A web-based cross-sectional, online survey was conducted among nursing undergraduates to assess the association of compulsive buying behavior, emotional distress, self-esteem, internet addiction, and impulsiveness using total enumerative sampling from February 2024 to April 2024. Data were collected using self-administered PBS, IAT, Rosenberg self-esteem scale, BIS-Brief, and DASS-21 scales. Descriptive and inferential statistics were used. Frequency distribution, Bivariate correlation, and Multiple regression analysis were also used. Results: There were 410 participants with valid responses, and 207 [50.5%] fell into the category of pathological buying. The participant group “with pathological buying” was comparable with the group “not having pathological buying” in terms of sociodemographic statistics, preferred modality of purchasing stuff, and the “duration of daily internet use”. However, the DASS-21 and IAT scores were significantly higher among the participants “with pathological buying”. On regression analysis, both DASS and IAT scores were predicting the PBS scores. Conclusion: There is a significant association between pathological buying with internet addiction and psychological distress, but not with self-esteem, and impulsivity.